2021
DOI: 10.3389/fsoc.2021.671856
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital From Professional Engineering Organizations and the Persistence of Women and Underrepresented Minority Undergraduates

Abstract: Professional engineering organizations (PEOs) have the potential to provide women and underrepresented and minoritized (URM) students with social capital (i.e., resources gained from relationships) that aids their persistence in their engineering undergraduate programs and into the workforce. We hypothesize that women and URM students engineering students who participate in PEOs are more likely to persist in their engineering major and that PEOs contribute to their persistence by providing them access to insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…Studies that examine the intersection of STEM department culture, women and URM student values, and social capital from alters who can help mitigate dissonance between department culture and women and URM student values offer insight into the structural factors shaping engineering persistence. Our research shows that women and URM students benefit from access to resources and advice from alters in students' social networks (i.e., network-based social capital), as well as alters in the organizations in which they participate (i.e., participatory social capital) (Skvoretz et al, 2020;Campbell-Montalvo et al, 2021;Puccia et al, 2021;Smith et al, 2021). For example, Puccia et al (2021) identified the role network-based social capital garnered from parents' advice played in students' declaration and persistence in their engineering majors.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Studies that examine the intersection of STEM department culture, women and URM student values, and social capital from alters who can help mitigate dissonance between department culture and women and URM student values offer insight into the structural factors shaping engineering persistence. Our research shows that women and URM students benefit from access to resources and advice from alters in students' social networks (i.e., network-based social capital), as well as alters in the organizations in which they participate (i.e., participatory social capital) (Skvoretz et al, 2020;Campbell-Montalvo et al, 2021;Puccia et al, 2021;Smith et al, 2021). For example, Puccia et al (2021) identified the role network-based social capital garnered from parents' advice played in students' declaration and persistence in their engineering majors.…”
Section: Introductionmentioning
confidence: 83%
“…Students can access various resources based on the PEOs they choose to join and through the department of their major. Alters from PEOs, who may not be in the individual's social network and might be less socially proximal, may often offer advice about classes and career-related skills (Smith et al, 2021).…”
Section: Theoretical Perspective: Cmes (Fit) and Social Capitalmentioning
confidence: 99%
See 3 more Smart Citations